2013
DOI: 10.5012/jkcs.2013.57.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Screening of Some Novel 2-[5-(Substituted phenyl)-[1,3,4]oxadiazol-2-yl]-benzoxazoles as Potential Antimicrobial Agents

Abstract: ABSTRACT. A series of some novel 2-[5-(substituted phenyl)- [1,3,4]oxadiazol-2-yl]-benzoxazoles were synthesized by using benzoxazole-2-carboxylic acid on reaction with thionyl chloride in presence of ethanol solvent at room temperature gave benzoxazole-2-carbonyl chloride, which is turned into benzoxazole-2-carboxylic acid hydrazide on reaction with hydrazine hydrate in ethanol solvent under reflux. The subsequent treatment of benzoxazole-2-carboxylic acid hydrazide with an appropriate aromatic carboxylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Benzoxazoles are regarded as a promising class of bioactive heterocyclic compounds that exhibit a range of biological activities such as antifungal, antibacterial, antiviral, anti-HIV, antihelmintic, antiinflammatory, etc. [11][12][13][14][15][16][17][18][19][20][21] . In continuation of our research work [22][23][24][25] , we report here the synthesis and biological activities of organophosphate phenoxy derivatives derived from 2-mercapto benzoxazole.…”
Section: Introductionmentioning
confidence: 99%
“…Benzoxazoles are regarded as a promising class of bioactive heterocyclic compounds that exhibit a range of biological activities such as antifungal, antibacterial, antiviral, anti-HIV, antihelmintic, antiinflammatory, etc. [11][12][13][14][15][16][17][18][19][20][21] . In continuation of our research work [22][23][24][25] , we report here the synthesis and biological activities of organophosphate phenoxy derivatives derived from 2-mercapto benzoxazole.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the nanocatalyst confirmed by XRD, SEM, TEM, N 2 adsorption-desorption, FTIR and EDS (Energy Dispersive Spectroscopy) techniques. In this method, initially, coumarin-3-carboxylates are synthesised from an ultrasonic reaction between a 2-aminophenol derivative (25) and diethyl malonate (26) by using MgFe 2 O 4 nanocatalyst. The synthesised nanocatalyst was applied in the preparation of 3benzoxazol-2-yl-chromen-2-one derivatives (29) through the reaction of different coumarin-3-carboxylates ( 27) and 2-aminophenol derivatives under ethanol at reflux (28) (Scheme 8).…”
Section: Mode Of Activationmentioning
confidence: 99%
“…The synthesis of the compound ( 8 ) began with commercially available benzoxazole‐2‐carboxylic acid ( 5 ). The benzoxazole‐2‐carbonyl chloride ( 6 ), the key intermediate, has been prepared in 69% yield by stirring a mixture of benzoxazole‐2‐carboxylic acid ( 5 ) and thionyl chloride in the presence of ethanol solvent at room temperature for 3 h, as in Scheme 2 [25] …”
Section: Introductionmentioning
confidence: 99%
“…Benzamides and benzoxazole derivatives are known to possess a wide array of biological activities such as anti‐inflammatory, anti‐bacterial, antifungal, anti‐convulsant, and analgesic activity . The literature data showed that benzamides and benzoxazole moiety (G–I) (Figure ) can be a potent template for COX‐2 inhibitory activity, with GI safety margins .…”
Section: Introductionmentioning
confidence: 99%